2005
DOI: 10.1016/j.jneuroim.2005.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Proliferating brain cells are a target of neurotoxic CSF in systemic autoimmune disease

Abstract: Brain atrophy, neurologic and psychiatric (NP) manifestations are common complications in the systemic autoimmune disease, lupus erythematosus (SLE). Here we show that the cerebrospinal fluid (CSF) from autoimmune MRL-lpr mice and a deceased NP-SLE patient reduce the viability of brain cells which proliferate in vitro. This detrimental effect was accompanied by periventricular neurodegeneration in the brains of autoimmune mice and profound in vivo neurotoxicity when their CSF was administered to the CNS of a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
25
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 106 publications
(113 reference statements)
5
25
0
Order By: Relevance
“…While the QNP-treated groups gained weight (from B42 g to B44 g) over 2 weeks, SAL-injected males showed comparable body weight (B40 g) at both time points (treatment by time: F(1,35) = 4.096, P = 0.05). As observed earlier, 13,32 brain mass was consistently lower in MRL-lpr than in MRL þ / þ mice (456710 vs 50876 mg; substrain: F(1,35) = 10.150, P < 0.01), and this was not significantly altered by the QNP treatment (47472 vs 51474 mg).…”
Section: Diseased Micesupporting
confidence: 81%
“…While the QNP-treated groups gained weight (from B42 g to B44 g) over 2 weeks, SAL-injected males showed comparable body weight (B40 g) at both time points (treatment by time: F(1,35) = 4.096, P = 0.05). As observed earlier, 13,32 brain mass was consistently lower in MRL-lpr than in MRL þ / þ mice (456710 vs 50876 mg; substrain: F(1,35) = 10.150, P < 0.01), and this was not significantly altered by the QNP treatment (47472 vs 51474 mg).…”
Section: Diseased Micesupporting
confidence: 81%
“…In the case of glutamate toxicity, anti-DNA antibodies may play an important role. These autoantibodies have recently been found to cross-react with central NMDA receptors in mice, producing neuronal apoptosis (DeGiorgio et al, 2001), and a similar IgG-mediated neurodegenerative event is proposed to occur in MRL-lpr brains (Sakic et al, 2005b). This causal relationship between NR2 receptor-reactive autoantibodies and brain damage has also been reported in NP-SLE patients (Omdal et al, 2005).…”
Section: Possible Mechanisms and Targets Of Brain Cell Deathmentioning
confidence: 74%
“…More specifically, the subventricular zone (Sakic et al, 2000b;Sidor et al, 2005), subgranual zone (Ballok et al, 2003, and substantia nigra (Ballok et al, 2004a), known to contain proliferative progenitor cells capable of neurogenesis (Yamashita et al, 2006;Suh et al, 2005;McGuire et al, 2001;Zhao et al, 2003), show signs of damage in these animals. CSF from diseased lupus mice is also cytotoxic to neurons and neuronal progenitor cells in vitro (Maric et al, 2001;Ballok et al, 2004a) supporting a link between toxic CSF IgG and neuronal/progenitor cell damage (Sidor et al, 2005;Sakic et al, 2005b). If in vitro findings are predictive of in vivo events, then autoimmune-induced lesions of germinal layers may reduce the developmental and regenerative capacity of MRL-lpr brains.…”
Section: Evidence Of Neuronal Death and Impaired Brain Growth/atrophymentioning
confidence: 93%
“…However, given that increased ventricle/brain area ratio, emergence of protuberances, and SGZ shrinkage occur mainly at the onset of autoimmune disease, this deficiency seems unlikely to account for these effects. Second, neuroinflammation is reported to disrupt neurogenesis ( More recently, we showed that cells from the C17.2 neural stem cell line and neurospheres from several mouse strains die when incubated with cerebrospinal fluid (CSF) from diseased MRL/lpr mice (Sakic et al, 2005b). Therefore, the pathogenic cascade in vivo may include drainage of circulating immune factors (e.g., activated cytotoxic lymphocytes, cytokines and/or autoantibodies) via breached blood-brain barrier into the CSF and diffusion into neighboring tissue, leading to subsequent detrimental effects on proliferative cells.…”
Section: Discussionmentioning
confidence: 99%